The basic education in Sweden and Brazil: Some similarities and differences - Brandão, Carlos da Fonseca [UNESP] (FapUNIFESP (SciELO), 2019)
This article proposes to analyze the basic education system of Sweden and to compare it with the basic education system of Brazil. We consider it relevant to compare the two systems of Basic Education, despite the significant differences between the two countries (culture, history, size, population density, etc.), since the quality indicators of basic education in Sweden are considerably better than Brazilians. Our objective is to show the main similarities and differences between the two systems of Basic Education. In order to do so, we first described the structure and functioning of the Swedish Basic Education system, little known to us Brazilians, so that, in our conclusions, we highlight the main similarities and differences between them. The methodology adopted was qualitative exploratory research, with a review of the literature of authors who work with comparative studies in the educational area.
A educação básica na suécia e no Brasil: Algumas semelhanças e diferenças
Keywords: Basic education; Comparative education; Swedish educational system